The mechanisms and consequences of parental coordination in Procellariiform seabirds - Gillies, N (2021)
Biparental care is a longstanding evolutionary conundrum. Why should parents continue to invest in their offspring cooperatively, when by abandoning their partner they can reap all the benefits with none of the work? Since the 1970s, several models have attempted to explain the evolution and maintenance of biparental care in animals, eventually converging on the solution of conditional cooperation: a parent’s behaviour should depend on the investment decisions of its partner. This responsive strategy can lead to apparent coordination between parents, and many empirical examples have since been reported. However, it is difficult to determine whether there is active behavioural coordination between parents, or indeed the mechanisms underlying it. This thesis uses two long-lived, monogamous seabird species, the Manx shearwater Puffinus puffinus and the black-browed albatross Thalassarche melanophris, to investigate the occurrence and mechanisms of coordinated parental behaviour. Using both experimental field manipulations and quantitative observations I investigated the evidence for parental coordination in these species, and the mechanisms and information parents may use to achieve it. Firstly, I examined the incubation behaviour of parent Manx shearwaters, and found that their investment decisions were underlain largely by their available body mass reserves, matching life-history predictions that long-lived species should be selected to prioritise their own condition. Specifically, foraging birds determined how long they should spend at sea by the amount of mass gains they needed to make on their trip, with lighter birds spending proportionally more time foraging. However, I found that this decision was modulated by the partner’s condition, with birds curtailing their trips when their partner was in poor condition, suggesting that cooperative processes, perhaps facilitated by a process of negotiation, may drive the coordination of care during incubation in this species. For chickrearing shearwaters, I examined whether direct communication, or indirect information garnered from the behaviour of the chick, might facilitate the coordination of nest visitation. Neither putative sources of information appeared necessary for coordination in this species, and it was not possible to determine conclusively what information drives provisioning behaviour. Instead, I introduced the possibility that coordination at this breeding stage emerges passively through an entrainment process during incubation. Finally, I investigated the potential role of intra-pair display in facilitating coordination in the black-browed albatross, with a focus on allopreening. I report tentative evidence that display forms part of an assessment process whereby the outgoing parent determines its partner’s willingness to invest in care, which may ultimately contribute to decision-making processes relating to foraging trip duration. Overall, I present evidence that biparental care in these species may be underlain by nuanced systems of intra-pair coordination, giving further insight into why and how animals are able to achieve cooperative behaviour.